ATRAVÉS DO ECRÃ:EAD PARA FORMAR PROFESSORES DE HISTÓRIA NO PARANÁ (UEPG 2008-2014) - Bitencourt, Suzana (2016)
This research analyzed the implementation of the History teaching degree from Pró Licenciatura (PROLICEN) and the Universidade Aberta do Brasil (UAB - Open University of Brazil). These are Federal Government programs designed to graduate more teachers to work in primary and secondary schools. The History teaching degreeoffered by the State University of Ponta Grossa (UEPG) was taken as the objective field of investigation. The main objective was to verify how the implementation of the course occured, seeking to understand how teaching and learning happened when mediated by technology, with the purpose of analyzing the impact of such a conception of education on the works of the pedagogical doings of those who teach, as well as those who learn. For that, we relied on sources of oral origin, with the aim of getting as close as possible to the daily lives of teachers and undergraduate students involved with Distance Education (DE). The methodology used included the theoretical contributions presentedin the theory of language of Mikhail Bakhtin (1997) and Lev Semenovitch Vygotsky (2000). The concept of mediation is particularly important as pedagogical mediation is a perspective widely used in the distance education theme. In this case, we intended to verify the practical application of mediation through the use of technology. The notion of social experience presented in Edward Palmer Thompson’s (1981) work headed the motivation of the research, as, from this, it was possible to reach the daily life of the subjects, contrasting official documents with evidence obtained oraly. The data analysed demonstrated that PROLICEN mobilized changes in academic teaching practices because it forged the use of pedagogical resources that were unaware to them, as well as access to the theoretical postulates of history, as they were teachers working in unsuitable areas of their education. This result allowed us to affirm that Distance Education has adequate applicability when used in continuing education. Being graduated by Distance Education for the graduated professionals was of great impact on teaching activities, as qualitative improvements in the practice of the classroom occured, the chances of understanding and using technologies in teaching increased and,above all, there was personal fulfillment due to the conquest of a specific degree in the professional area, previously carried out without the necessary qualification. Regarding the UAB, this program worked more broadly in terms of enrollment offer, by not reaching only teachers in service. This research showed that the technologies in education, in most cases, are used out of compulsion. For effectiveness of Distance Education, the collected results indicate the need for a more versatile education proposal that combines face to face and distance models.